Environmental Political Model and Deforestation Analysis in South Kalimantan, Indonesia - Andi Tenri Sompa; Arif Rahman Hakim; Dinar Adis Tiyani; Safa Muzdalifah (International Journal of Politic, Public Policy and Environmental Issues, 2021)
In Banjar Regency, South Kalimantan, Indonesia, there has been a reduction in the forest area of ​​32,209.24 hectares over the last 10 years. The area experiencing deforestation is on the east side of Banjar Regency which is one of the production forest areas. Environmental change does not occur naturally but is an implication of the socio-political aspects that surround it. This study aims to explain the model of environmental politics in the context of deforestation in the Banjar Regency. The theory used is the theory of political systems from Gabriel Almond and the concept of environmental politicization. The research method used is descriptive qualitative. The type of data is in the form of secondary data related to legal documents on forest management authority, and primary data in the form of findings on the characteristics of actors and the motives of the interests of the actors involved in them. The informants of this research include elements of the South Kalimantan provincial government, the district government, the Environmental Care Community, and local community groups. The results show that the environmental politics model in the context of deforestation in Banjar Regency is centralized. The centralized political environment model is a model that shows the alternating political currents that ultimately refer to the interests of the central government. This interest is oriented towards forest management to support the acceleration of national economic growth.